2022
DOI: 10.1097/mcp.0000000000000915
|View full text |Cite
|
Sign up to set email alerts
|

More than sleepiness: prevalence and relevance of nonclassical symptoms of obstructive sleep apnea

Abstract: Purpose of reviewThe purpose of this review is to describe the nonclassical symptoms and manifestations occurring in patients with obstructive sleep apnea (OSA), both from a standpoint of prevalence and in terms of clinical relevance. Particular emphasis will be given to nightmares, comorbid insomnia, restless legs syndrome and periodic limb movement disorder, bruxism, morning headache, nocturia, acid reflux, chronic cough and dysphagia. Recent findingsA review of the recent literature suggests that nonclassic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 93 publications
0
7
0
Order By: Relevance
“…These results clearly indicate the need for cooperation between pneumonologists and psychiatrists, as the result of cooperative treatment will provide the best healthcare for the patient. In contrast to this statement, there is also a large body of evidence that the correlation between psychological disease and the OSA level is not sufficiently explained, and conduction of larger clinical studies on this topic would be useful for further guidelines [3,4].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…These results clearly indicate the need for cooperation between pneumonologists and psychiatrists, as the result of cooperative treatment will provide the best healthcare for the patient. In contrast to this statement, there is also a large body of evidence that the correlation between psychological disease and the OSA level is not sufficiently explained, and conduction of larger clinical studies on this topic would be useful for further guidelines [3,4].…”
Section: Discussionmentioning
confidence: 95%
“…The negative influence of OSA on the patient's quality of life is properly documented by numerous studies. Except the physical health itself, OSA has a great impact on mental health and emotional status, and several studies confirmed that OSA may even worsen the bed partner's quality of life due to snoring during the night and consequently decrease the energy and vitality of the bed partner [2][3][4]. The disease rate is slightly higher in the male population and has not changed significantly in the previous decade [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another area for improvement involves the absence of standardized calculation methods for CPAP indices across manufacturers [51], along with the necessity for thorough validation of devices utilized in multimodal telemonitoring of various health-related parameters [45]. Finally, numerous regulatory matters concerning data safety and healthcare regulation remain unresolved, and additional enhancements should concentrate on delineating the pertinent data for medical diagnosis and follow-up purposes [77].…”
Section: Pitfalls Of Telemedicinementioning
confidence: 99%
“…Recently more studies have been focusing on the psychiatric aspects of this disorder, i.e., increased prevalence of affective diseases (particularly depression), cognitive impairment, or co-existing insomnia. The prevalence of this condition in patients with OSA in some studies reaches up to 84% [ 14 ]; it might greatly affect a patient’s prognosis and overall health as well as affect adherence to treatment and its potential effectiveness [ 15 , 16 , 17 ]. In one study, the risk of all-cause mortality in the OSA group with comorbid insomnia was 47% higher than non-insomnia OSA controls [ 18 ].…”
Section: Introductionmentioning
confidence: 99%